Alvaro Mutis and the Ends of History - Gerald Martin (Studies in 20th & 21st Century Literature, 1995)
Part of the confusion of the current literary and critical moment, in Latin America and elsewhere, involves a debate as to whether the most characteristic forms of contemporary writing are the more apparently transparent (in contrast to current critical practice) or the more impenetrable and indecipherable of literary texts. This debate is of particular relevance to Latin American discussions about the so-called "Post-Boom," and the work of the Colombian Alvaro Mutis, a writer who came late to narrative fiction and to critical attention, offers several insights into the links between writing, criticism and idology at this moment close to the end of the century and even, so some thinkers have said, to the end of history.
Keywords: Colombian literature; Alvaro Mutis; literary analysis; literary criticism; power-boom; writing; criticism; ideology; labyrinth; end of history; history